Given that:
f(x) =
1/(x-1)(x-2)
We need to find
f'(0)
First we need to find the first derivative
f'(x).
Let f(x) = 1/(x-1) *(1/(x-2) =
u*v
such that:
u = 1/(x-1)
==> u' = -1/(x-1)^2
v= 1/(x-2) ==> v' =
-1/(x-2)^2
==> We will use the product rule to
determine f'(x).
==> f'(x) = u'*v +
u*v'
= (-1/(x-1)^2 * 1/(x-2) + (1/(x-1)
*(-1/(x-2)^2
= -1/(x-2)(x-1)^2 -
1/(x-1)(x-2)^2
= ( -(x-2) - (x-1) /[
(x-1)(x-2)]^2
=
(-x+2-x+1)/[(x-1)(x-2)]^2
=
(-2x+3)/[(x-1)(x-2)]^2
==> f'(x) =
(-2x+3)/[(x-1)(x-2)]^2
==> f'(0) = 3/
(-1)(-2)]^2
=
3/4
==> f'(0) =
3/4
No comments:
Post a Comment